KONTRIBUSI ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KINERJA UKM - K. Mawardi, Mukhammad (Profit: Jurnal Adminsitrasi Bisnis, 2007)
The business competition drives the SMEs to create competitive advantages, which are influenced by external and internal factors. Entrepreneurship Orientation is one of the internal factors that contribute to business performance. Entrepreneurship orientation contributes to business performance through market orientation and organizational structure. This research investigated relationships between entrepreneurship proclivity, market orientation and business performance. This explanatory research used path analysis to analyze quantitative data were collected using questionnaire. All owners and managers of SMEs in sanitair industry in Karang Besuki —Malang. The results indicate that relationship between innovation and market orientation are not significant, relationship between risk taking and proactive attitudes to market orientation is significant. Innovation and risk taking attitudes directly contribute to business performance, but the proactive attitude indirectly contributes to business performance through market orientation.Keywords: Entrepreneurship Orientation, Market Orientation, Business Performance